A simple and reliable technique to design kinematic-based sideslip estimators. (March 2020) - Bascetta, Luca; Baur, Marco; Ferretti, Gianni
Abstract: This paper proposes two novel vehicle sideslip estimators, that aim at achieving ease of implementation and tuning, low computational cost and robustness, using only the most common automotive measurements, like vehicle position, acceleration and rotational velocity. The two estimators are only based on the unicycle kinematic model, thus they do not require any knowledge of uncertain or time-varying parameters, like vehicle parameters, or of road conditions, as it usually happens when dynamic models are adopted, and they have been derived by recasting an estimation problem into a linear control problem. Different experiments, ranging from standard driving manoeuvres to drifting driving and autonomous driving, have been performed to demonstrate the effectiveness of the proposal even in particularly critical scenarios, like driving at the limits of vehicle's handling. A comparison with a state-of-the-art sideslip estimator, using simulation and experimental data, is presented, as well. Highlights: Two novel vehicle sideslip estimators are proposed. Characterised by ease of implementation and tuning, low computational cost, robustness. Using only the most common automotive measurements. Experimentally tested on standard and drifting driving manoeuvres.